Exploring Bayesian model averaging with multiple ANNs for meteorological drought forecasts - Achite M.; Banadkooki F.B.; Ehteram M.; Bouharira A.; Ahmed A.N.; Elshafie A. (Springer Science and Business Media Deutschland GmbH, 2023)
Atmospheric pressure; Bayesian networks; Climatology; Drought; Neural networks; Water management; Weather forecasting; ANN; Bayesian model averaging; Meteorological drought; Optimization algorithms; Salp swarms; Sine-cosine algorithm; Standardized precipitation index; Swarm algorithms; Water resources management; Water striders; Particle swarm optimization (PSO); accuracy assessment; algorithm; artificial neural network; Bayesian analysis; drought; El Nino-Southern Oscillation; North Atlantic Oscillation; optimization; Pacific Decadal Oscillation; precipitation assessment; Southern Oscillation; weather forecasting